2021
DOI: 10.1007/s11682-021-00560-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered structural brain networks in linguistic variants of frontotemporal dementia

Abstract: Semantic (svPPA) and nonfluent (nfvPPA) variants of primary progressive aphasia (PPA) have recently been associated with distinct patterns of white matter and functional network alterations in left frontoinsular and anterior temporal regions, respectively. Little information exists, however, about the topological characteristics of gray matter covariance networks in these two PPA variants. In the present study, we used a graph theory approach to describe the structural covariance network organization in 34 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…The global brain network organization of patients with svPPA was characterized by a decreased global efficiency and clustering coefficient, and a higher characteristic path length ( 15 , 22 ), which could reflect lower segregation and integration in the overall network organization. This finding was also confirmed by a recent study showing a reduced small-worldness index in the structural brain network of patients ( 28 ). At a local level, a reduced nodal efficiency, degree, and clustering coefficient have been observed in several brain regions, including the left middle and superior temporal gyri, entorhinal cortex, amygdala, fusiform, hippocampus, and insula ( 15 , 28 ).…”
Section: Network Alterations In Patients With Ftdsupporting
confidence: 85%
See 3 more Smart Citations
“…The global brain network organization of patients with svPPA was characterized by a decreased global efficiency and clustering coefficient, and a higher characteristic path length ( 15 , 22 ), which could reflect lower segregation and integration in the overall network organization. This finding was also confirmed by a recent study showing a reduced small-worldness index in the structural brain network of patients ( 28 ). At a local level, a reduced nodal efficiency, degree, and clustering coefficient have been observed in several brain regions, including the left middle and superior temporal gyri, entorhinal cortex, amygdala, fusiform, hippocampus, and insula ( 15 , 28 ).…”
Section: Network Alterations In Patients With Ftdsupporting
confidence: 85%
“…This finding was also confirmed by a recent study showing a reduced small-worldness index in the structural brain network of patients ( 28 ). At a local level, a reduced nodal efficiency, degree, and clustering coefficient have been observed in several brain regions, including the left middle and superior temporal gyri, entorhinal cortex, amygdala, fusiform, hippocampus, and insula ( 15 , 28 ). Moreover, a loss of hubs was observed in left-hemisphere regions ( 15 ).…”
Section: Network Alterations In Patients With Ftdsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with these studies, our study showed a prominent involvement of the caudal middle frontal gyrus, pars opercularis regions and caudate for PNFA vs. the controls classification model. Similarly, predominant involvement of temporal brain regions, i.e., temporal pole, hippocampus, and amygdala, was also observed for the classification between svPPA and control ( Gorno-Tempini et al, 2004 ; Rohrer et al, 2009b ; Bocchetta et al, 2019 ; Nigro et al, 2021a ).…”
Section: Discussionmentioning
confidence: 54%